EFEKTIVITAS MEDIA CETAK POSTER DALAM MENINGKATKAN PENGETAHUAN PETANI TENTANG PENGENDALIAN HAMA PENYAKIT TANAMAN PADI SAWAH DI DESA LAMBUDONI KECAMATAN ANDOWIA KABUPATE KONAWE UTARA - Disahrani Putri Wulandari; Ima Astuty Wunawarsih; Salahuddin Salahuddin; Darsilan Dima (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The objective of this study is to ascertain the efficacy of printed media, specifically posters, in enhancing farmers' understanding of pest and disease control in paddy rice plants. The study population consisted of all rice farmers in Lambudoni Village, Andowia Subdistrict, with a total of 187 farmers comprising nine farmer groups. The number of research samples was determined using the Slovin formula with a degree of error set at 15% (0.15), resulting in a sample size of 36 respondents. The research sample was selected through the use of the simple random sampling method. The data collection techniques involved the distribution of posters regarding the control of pests and diseases of paddy rice plants, accompanied by a list of questions in the form of a questionnaire. The data were subjected to descriptive and quantitative analysis. This research was designed as a true experimental design with a pre-test post-test control group. Subsequently, the efficacy of the media can be evaluated through the implementation of a media effectiveness test. The results demonstrated that the utilization of printed media in the form of posters in agricultural extension activities, with a composition of 60:40 (picture: writing), has been proven to be an effective approach in enhancing the knowledge of wetland rice farmers in controlling pests and diseases in Lambudoni Village, Andowia District, North Konawe Regency. The composition of a poster is an important factor in conveying messages and extension information to farmers. The use of images on a poster can help farmers to focus more on the information presented and to understand the content more easily.